The incidence of neuropathic pain in bone metastases patients referred for palliative radiotherapy. Issue 3 (March 2016) - Lechner, Breanne; Chow, Selina; Chow, Ronald; Zhang, Liying; Tsao, May; Danjoux, Cyril; Barnes, Elizabeth; DeAngelis, Carlo; Vuong, Sherlyn; Ganesh, Vithusha; Chow, Edward
Abstract: Background and purpose: To estimate the prevalence of neuropathic pain in patients with symptomatic bone metastases referred for palliative radiotherapy. Material and methods: A prospective study of patients with symptomatic bone metastases was conducted. Patients referred for palliative radiotherapy completed the Self-Reported Leeds Assessment of Neuropathic Symptoms and Signs (S-LANSS) questionnaire to assess for neuropathic pain. Patient demographics, medication use, and radiotherapy prescribed were collected. Statistical approaches to identify relationships between the presence of neuropathic and other patient factors were conducted. Results: 62 patients completed the S-LANSS and 16 (25.8%) patients had a score suggesting neuropathic pain. Fifty-nine (95.2%) patients received radiotherapy with total of 81 sites treated, the most common sites were spine and pelvis. No statistically significant difference in fractionation was found between patients with and without neuropathic pain. Of the 16 patients with neuropathic pain, only 2 were receiving a neuropathic specific analgesic. No significant difference between demographic factors or radiation treatments between patients with and without neuropathic pain was found. There was no significant difference in worst pain score between these two groups. Conclusions: Pain with neuropathic features remains prevalent in a population of patients referred for palliative radiotherapy. More frequent prescription of pain medications targeting neuropathic pain may be warranted in this patient population.